Escola de auxiliar de enfermagem Dr. Mário Corrêa da Costa : a profissionalização da enfermagem em Mato Grosso (1952-1975) - Borralho, Lidiana Laura Campos (2012)
There was an impulse in the health national policies which began in the 1930s, that aimed at the prevention of epidemics that were spreading all over the country. For this reason, in that decade, the Education and Health Ministry was created and was responsible for the deep changes in all the federative units and also in Mato Grosso. The nursing care in the state, since the XIXth century, was practiced by laymen, slaves and clergy, without previous qualification for the professional exercise in the area. In order to overcome the lack of nursing qualified professionals, educational institutions for the formation of these professionals were created, such as the Schools for Nursing Assistants Dr. Mário Corrêa da Costa, founded in Mato Grosso through Law no. 417, of September 17, 1951. This school, during its trajectory, was housed in several buildings, starting to function in the Hospital and Maternity Center of Cuiabá in 1952, and closing in 1975 in the Presidente Médici State School. This paper is about the analysis of creation and functioning of the School for Nursing Assistants Dr. Mário Corrêa da Costa Cuiabá-MT, during the period between the implantation and the closing of its educational activities between the 1950s and 1970s. The research lies in the History of Education field and includes an analysis of the documental sources available in the Public Archive of Mato Grosso, the Archive of Casa Barão de Melgaço, of the President Medici State School, as well as the sources that belong to the private document collection of the first Nurse of the state, Adelaide de Almeida Orro, stored in the state archive. An interview with the same nurse and an ex-student of the School for Nursing Assistants Dr. Mário Corrêa da Costa, Mrs Ana Iraci Longo was carried out. Although the School Dr. Mário Corrêa da Costa had not been the first institution to qualify nursing professionals in Mato Grosso, it stood out due to its official characteristic, being qualified as “apple of the eyes” of the governor Fernando Corrêa da Costa. This school had a fundamental role in the training of basic level professionals in the State, for many years it was headquarter of the Brazilian Association of Nursing Assistants of Mato Grosso – ABEn-MT. The documental sources pointed that the School of Nursing Assistants Dr. Mário Corrêa da Costa played an important role in the trajectory of Nursing in Mato Grosso, having been very important for the creation and establishment of the Nursing Course in the Federal University of Mato Grosso – UFMT.